Pediatric orbital fractures in Singapore: demographics, etiology, and the role of bioresorbable implants - Boniao, Emmanuel Lee; Gungab, Alexander; Lim, Blanche Xiao Hong; Sundar, Gangadhara (Frontiers in Ophthalmology, 2025)
PurposeThis study aimed to analyze the demographic characteristics, etiology, fracture types, interventions and treatment outcomes, with a focus on the increasing role of bioresorbable implants compared to traditional non-resorbable implants in pediatric orbital fractures.MethodsThis was a retrospective cohort study conducted at the Department of Ophthalmology, National University Hospital, Singapore, of pediatric patients (aged 18 years or younger) treated surgically for orbital fractures from January 2005 to May 2023. Data was extracted from the hospital’s electronic medical records, including demographic details, causes of fractures, types of fractures, implants used (bioresorbable and non-bioresorbable), and clinical outcomes.Results43 cases of pediatric orbital and orbitofacial fractures met the criteria undergoing surgical intervention. Most occurred in males (81.4%, n=35). Causes of fractures were sports-related incidents and play (46.5%, n=20), assault (30.2%, n=13), road-traffic accidents (16.3%, n=7), and non-play related accidents (7%, n=3). Most pediatric orbital fractures were unilateral (88%, n=38). While most were pure or simple orbital fractures (74.4% n=32), 25.6% (n=11) were complex orbitofacial fractures. Amongst simple orbital fractures, blowout fractures (91%, n=29) were the most common, involving the inferior (58.6%, n=17), combined floor and medial wall (20.6%, n=6), medial wall (13.8%, n=4) and roof (6.9%, n=2). Amongst the complex fractures, zygomaticomaxillary complex fractures were the most frequent (45.4%, n=5), followed by cranioorbital fractures (27.3%, n=3) and Le Fort II & III fractures (27.3%, n=3). Orbital tissue entrapment was common (56%, n=24), and most patients with entrapment underwent urgent surgical intervention (65%, n=28), usually within 24 hours (53%, n=23). The majority of those who underwent surgery had implants placed (89%, n=25), with most being bioresorbable (64.3%, n=18). All patients (100%) who underwent surgery showed clinical improvement without significant complications.ConclusionAlthough simple pediatric orbital blowout fractures are still the most common among pediatric patients, the study showed that a quarter of them presented with complex orbitofacial fractures requiring multidisciplinary management. Most fractures occurred in males and typically associated with increasing play and physical activity in teenagers. The study also showed that early intervention is crucial to better outcome, with the increasing role of bioresorbable implants in this population reducing long term implant related complications.